(untitled) (Texas Journal of Medical Science, 2025)
The clinical pharmacological approach to the use of antiarrhythmic drugs in children is crucial for ensuring effective and safe treatment of cardiac arrhythmias. This article explores the classification, mechanisms of action, indications, contraindications, and potential adverse effects of commonly used antiarrhythmic agents in pediatric patients. Special attention is given to the pharmacokinetics and pharmacodynamics of these drugs in children, considering age-related differences in drug metabolism and response. The importance of individualized therapy, monitoring strategies, and recent advancements in pediatric cardiology are also discussed